Strategy formulation for the sustainable development of smart cities: a case study of Nanjing, China - Yuan, Jingfeng; Xie, Hong; Yang, Dujuan; Xiahou, Xiaer; Skibniewski, Mirosław J.; Huang, Wei (International Journal of Strategic Property Management, 2020)
Smart cities possess huge potential in future urban development. However, the critical problems in developing sustainable smart cities in China are the lack of clear strategies and effective strategy planning tools. Therefore, reasonable plans and strategies play important roles in helping the government develop sustainable smart cities. In this study, 16 SWOT (Strength, Weakness, Opportunity, and Threat) factors were identified. According to a structured questionnaire survey about SWOT factors, an integrated method, composed of SWOT and AHP (analytic hierarchy process) was conducted. A case study was conducted in Nanjing, China. The most powerful facilitators (strengths and opportunities) and the most powerful obstacles (weaknesses and threats) for developing Smart Nanjing City (SNC) were identified. The strategic intensity and value of the elements were confirmed. Moreover, proactive strategies were proposed including strengthening intelligent clusters, establishing governance ecosystem, and providing integrated services for SNC, which can be considered as policy suggestions for SNC, providing hybrid strategies for a planning approach integrating bottom-up and top-down design to develop smart cities, as a reference for other global cities. Moreover, the proposed AHP-SWOT hybrid method can be used as an effective quantitative strategy planning tool to help other authorities determine appropriate strategies for developing smart cities.